2017
DOI: 10.1002/mrm.26772
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria‐targeted antioxidant MitoQ reduced renal damage caused by ischemia‐reperfusion injury in rodent kidneys: Longitudinal observations of T2‐weighted imaging and dynamic contrast‐enhanced MRI

Abstract: PurposeTo investigate the effect of mitochondria‐targeted antioxidant MitoQ in reducing the severity of renal ischemia‐reperfusion injury (IRI) in rats using T2‐weighted imaging and dynamic contrast‐enhanced MRI (DCE‐MRI).MethodsIschemia‐reperfusion injury was induced by temporarily clamping the left renal artery. Rats were pretreated with MitoQ or saline. The MRI examination was performed before and after IRI (days 2, 5, 7, and 14). The T2‐weighted standardized signal intensity of the outer stripe of the oute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…Hueper et al established a mouse model of renal IRI and indicated that increases in the T 2 signal of the kidney were associated with cell edema caused by acute renal injury after renal IRI 9 . Liu et al investigated the effect of mitochondria‐targeted antioxidant MitoQ on renal IRI in a rat model using T 2 WI, showing that the increase in the T 2 signal of the kidney may be related to the tissue edema and increased water content caused by reperfusion 22 . In this study, T 2 WI_S(3,‐3)InvDfMom had the strongest correlation with brush border destruction, tubular epithelial edema, necrosis, and cast, and it gradually increased from 1 to 24 hours after reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Hueper et al established a mouse model of renal IRI and indicated that increases in the T 2 signal of the kidney were associated with cell edema caused by acute renal injury after renal IRI 9 . Liu et al investigated the effect of mitochondria‐targeted antioxidant MitoQ on renal IRI in a rat model using T 2 WI, showing that the increase in the T 2 signal of the kidney may be related to the tissue edema and increased water content caused by reperfusion 22 . In this study, T 2 WI_S(3,‐3)InvDfMom had the strongest correlation with brush border destruction, tubular epithelial edema, necrosis, and cast, and it gradually increased from 1 to 24 hours after reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…MitoQ is a derivative of ubiquinone which linked to TPP moiety by a 10-carbon alkyl chain (Murphy and Smith, 2007 ). Much information indicates that the ubiquinol moiety of MitoQ can react with superoxide and protect against peroxynitrite (Liu et al, 2018b ). Animal studies have revealed that MitoQ protects against oxidative damage such as hypertension (Pak et al, 2018 ) and neurodegenerative disease (Yin et al, 2016 ).…”
Section: Role Of Antioxidants In the Prevention Of Age-related Diseasmentioning
confidence: 99%
“…In the mitochondria ubiqinone is reduced to ubiquinol, a powerful ROS scavenger. Administration of MitoQ in renal I/R models resulted in reduced markers of oxidative stress, reduced renal injury and improved function [28][29][30]. Regarding the mitochondrial targeted proteins, the Szeto-Schiller (SS) proteins are the best known.…”
Section: Reperfusionmentioning
confidence: 99%